A Critical Analysis of the Implications of the Policy on Higher Education Institutions as Legal Entities for Access to Education and Social Justice in Indonesia - Rizki Gagah Perkoso; Dedy Hartanto; Juliansyah Juliansyah; Widyatmike Gede Mulawarman; Akhmad Akhmad (Universitas Muhammadiyah Mataram, 2026)
Higher education plays a strategic role in promoting social mobility and equal opportunity; however, policy transformation through State Universities with Legal Entity status (PTN-BH) has introduced new dynamics in the relationship between institutional autonomy, access to education, and social justice. This study aims to critically examine the construction of the PTN-BH policy and its implications for access to higher education and social justice in Indonesia. The study employs a qualitative approach using a Critical Literature Review (CLR) design, analyzing journal articles indexed in SINTA and Scopus from 2018 to 2025. The analysis is conducted through a semi-systematic literature selection process, thematic coding, and critical synthesis, guided by the frameworks of distributive justice, the capability approach, and social reproduction theory. The findings indicate that the PTN-BH policy reflects a shift from state-centered governance to market-oriented governance, resulting in a form of hybrid governance. While institutional autonomy encourages funding diversification, it simultaneously increases educational costs and reliance on student contributions. This condition leads to a pattern of selective inclusion, in which access to higher education remains formally open but is substantively filtered by economic capacity. Furthermore, the policy contributes to the reproduction of social inequality, as financial resources increasingly determine access to higher education. Overall, the PTN-BH policy reveals a structural tension between efficiency and social justice. Without adequate redistributive mechanisms, this policy risks reinforcing stratified access and shifting the role of higher education from a vehicle of social mobility to a mechanism of inequality reproduction. Therefore, policy reformulation is required to balance institutional autonomy with the principles of social justice in order to achieve a more inclusive and sustainable higher education system.